(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
The researcher come up in creating a delicious dessert which is yema with a twist of ampalaya, many people especially children, didn’t like the taste of ampalaya in that way the researcher conclude that, what if we create a dessert with a mix of vegetable on it. And the researcher decided to do a dessert that is very common nowadays and it so affordable and very flexible in all the demand in the market. Nowadays many people want to have a business, but not all have the will to become successful in that field and the researcher decided to build a store for them to share their unique ideas about the new dessert discovered, and in that way they can give a chance for many parent to patronize the researcher store can give them a chance to feed their children a healthy and delicious food. The researcher use a survey because it easily find a respondent and the researcher can easily formulate a conclusion after having a survey in random places, and we as the researcher formulate a specific question to be answered by the respondent and they can give a result the serves as the researcher basis in the research. The researcher got a result by simply analyzing the data they gathered after conducting a survey they use it as their basis and for them justify their further conclusion about the research. In the data gather most of them agree by simply answered yes in the question in the survey which is having a percentage of 60% and the other 40% disagree in the question in the survey.The researcher wanted to change all the negative thoughts we write in the research and we cannot do it without any of your guide. We want to change the process that we create in the product because the product that has been created in very low in appearance.